A mandate to self archive? The role of open access institutional repositories - Pinfield, Stephen (UK Serials Group, 2005)
This paper argues that the best way to achieve major improvements in scholarly communication in the short and medium term is to make it mandatory to deposit research papers in open access institutional repositories. This is what the House of Commons Science and Technology Committee report of 2004 on scientific publishing recommended. The paper defines what open access repositories are and explains why they should be institutional. It also deals with question of what should be deposited in institutional repositories and why these improve scholarly communication. It then deals with the issue of mandating deposition: why deposition should be mandatory, who should mandate deposition and who should carry out deposition. The paper concludes with an analysis of the wider implications of mandating deposition in institutional repositories and a summary of the existing situation in the UK and elsewhere. The paper discusses the Select Committee report and the UK Government response in relation to institutional repositories.